ANALISIS PROFITABILITAS USAHA PEMBUATAN ABON IKAN TUNA ( Studi Kasus Pada Usaha Wanita Mandiri ) DI KELURAHAN SIDOARJO KECAMATAN BAOLAN KABUPATEN TOLITOLI - Nurmala Nurmala; Dewi Triana; Sutomo Mokodompit; Alumi Alumi (Universitas Tadulako, 2019)
This research was conducted in Sidoarjo village, Baolan subdistrict, Tolitoli district with the purpose of determining the profitability of tuna fish shredded business based on Return on Investment (ROI) and Profit Margin.. The population of this study was the entrepreneurs of the tuna shredded belong to the women self-sustained businesses present in Sidoarjo village, Baolan subdistrict, Tolitoli district. Data analyzed was depicted descriptively. In 2015, the total production costs incurred was IDR 26,379,996 and the revenue was IDR 37,695,000. The profitability analysis based on the ROI was 42.89% meaning that for every IDR 100,000 of the capital invested in the tuna business generates a profit of IDR 42,890. Whereas based on the profit margin achieved by the tuna shredded business was 30.01% meaning that for every IDR 100,000 spent results in a profit of IDR. 30,010.